Quality of Public Services (A Study of General Polyclinic Services at the Loea Community Health Center, Loea District, East Kolaka Regency) - Irjal Nasrul (Teras Kampus, 2026)
This study aims to describe the quality of public services in public poly services at the Loea Health Center, Loea District, East Kolaka Regency, Southeast Sulawesi, Indonesia. This study uses a qualitative descriptive method. Informants were selected purposively, namely the head of the Health Center, general practitioners, nurses, administrative officers, as well as patients. The types and sources of data used are primary data, collected directly through observation, interviews, and documentation, as well as secondary data, which includes relevant previous documents and research. Data analysis was carried out using the interactive model. The results of the study show that tangible aspects of public poly services still require an increase in adequate physical facilities, such as the addition of waiting chairs. Reliability is hampered by the limited number of employees and the presence of healthcare providers who arrive late, which leads to long queues of patients. Responsiveness has not been maximized because the number of doctors and nurses is limited and the picket or guard system is still in place. Assurance is also not evenly distributed because health programs have not been able to reach all levels of society, so many do not know about the health programs carried out by the Health Center. Empathy has not been implemented properly, and the provision of attention and convenience in serving the needs of the community has not been fully based on the needs of patients. Overall, the quality of public services at the Loea Health Center has not been optimal, causing patient dissatisfaction.